Questioning Skills For Teachers And Students: The Importance And Implementation - Muhammad Nur Huda (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2022)
Humans are creatures who are never satisfied with the search for truth by constantly asking questions to meet their needs. The skill of asking questions needs to be possessed by everyone for it is one of the important skills to compete in the 21st century. In philosophy, humans ask everything from various angles, in totality, regarding the essence of the core, the cause from the cause, looking for a path to, to the bottom. In education, a teacher needs to have the skills to ask questions so that they can interact and provoke the curiosity of their students. In the activity of teaching and learning, the application of questioning skills is a very effective strategy for analyzing and exploring students' fresh ideas. Spontaneous questions asked by students can be used to make them think, be creative, and speculate. Teachers' efforts to improve skills can be done by implementing class discussions by dividing students into several groups and asking each other. In addition, enhanching question skills could be acquired from presenting activities that encourage the scientific process, activities that are adapted to the development of students, as well as providing high-level questions or open-ended questions that can bring up many answers.